Multidimensional Egalitarianisms - Kolm, Serge-Christophe (Quarterly Journal of Economics, 1977)
I. Specificism, 2.—II. Strong egalitarianism, 3.—III. Income and specific egalitarianism. 7.—IV. Equalizations. 8.—V. Proofs of the theorems. 9.